Prescribed form of record for a large raised reservoir Reservoirs Act 1975. (Thomas Telford, 1985)
Topics covered include water levels and depth of water; leakages, settlement of walls or other works and repairs; re-use, abandonment and discontinuance of reservoirs; spillway works; measures taken in the interest of safety, and more.
Keywords: Great Britain. -- Reservoirs Act 1975.; Reservoirs -- Law and legislation -- Great Britain.; Civil engineering.; elektronické knihy; electronic books